In situ monitoring of competitive coformer exchange reaction by 1H MAS solid-state NMR - Hareendran, Chaithanya; Alsirawan, Bashir; Paradkar, Anant; Ajithkumar, T. G. (Molecualr Pharmaceutics, 2024)
In a competitive coformer exchange reaction, a recent topic of interest in pharmaceutical research, the coformer in a pharmaceutical cocrystal is exchanged with another coformer that is expected to form a cocrystal that is more stable. There will be a competition between coformers to form the most stable product through the formation of hydrogen bonds. This will cause destabilization of the pharmaceutical products during processing or storage. Therefore, it is important to develop a mechanistic understanding of this transformation by monitoring each and every step of the reaction, employing a technique such as H-1 nuclear magnetic resonance (NMR). In this study, an in situ monitoring of a coformer exchange reaction is carried out by H-1 magic angle spinning (MAS) solid-state NMR (SSNMR) at a spinning frequency of 60 kHz. The changes in caffeine maleic acid cocrystals on addition of glutaric acid and caffeine glutaric cocrystals on addition of maleic acid were monitored. In all of the reactions, it has been observed that caffeine glutaric acid Form I is formed. When glutaric acid was added to 2:1 caffeine maleic acid, the formation of metastable 1:1 caffeine glutaric acid Form I was observed at the start of the experiment, indicating that the centrifugal pressure is enough for the formation. The difference in the end product of the reactions with a similar reaction pathway of 1:1 and 2:1 reactant stoichiometry indicates that a complete replacement of maleic acid has occurred only in the 1:1 stoichiometry of the reactants. The polymorphic transition of caffeine glutaric acid Form II to Form I at higher temperatures was a crucial reason that triggered the exchange of glutaric acid with maleic acid in the reaction of caffeine glutaric acid and maleic acid. Our results are novel since the new reaction pathways in competitive coformer exchange reactions enabled understanding the remarkable role of stoichiometry, polymorphism, temperature, and centrifugal pressure.
Keywords: caffeine cocrystal; coformer exchange reaction; in situ monitoring; polymorphism; Solid-state NMR